Fractional Integral Inequalities for Some Convex Functions - Bayraktar, B.R.; Attaev, A.Kh. (KU Publ., 2021)
In this paper, we obtained several new integral inequalities using fractional Riemann-Liouville integrals for convex s-Godunova-Levin functions in the second sense and for quasi-convex functions. The results were gained by applying the double Hermite-Hadamard inequality, the classical Holder inequalities, the power mean, and weighted Holder inequalities. In particular, the application of the results for several special computing facilities was given. Some applications to special means for arbitrary real numbers: arithmetic mean, logarithmic mean, and generalized log-mean, are provided.
Кейбір дөңес функциялар үшін бөлшекті-интегралдарды теңсіздіктер
Дробно-интегральные неравенства для некоторых выпуклых функций
Keywords: integral inequalıty; Hermite-Hadamard inequalitiy; convex function; s-Godunova-Levin convex; quasiconvex; fractional integral; H¨older inequality; power mean inequality